2001
DOI: 10.1042/ba19990015
|View full text |Cite
|
Sign up to set email alerts
|

Papain immobilization on a nitrilon fibre carrier containing primary amine groups

Abstract: A carrier containing primary amine groups was synthesized by the reaction between nitrilon fibre and diethylenetriamine, and papain was immobilized on this kind of carrier by using glutaraldehyde as a coupling agent. The factors involved with the activity recovery of the immobilized papain and the enzymic properties of the resulting immobilized papain were studied in comparison with free papain, for which casein was chosen as a substrate. The results show that the activity recovery of immobilized papain can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…K m is increased 10 times due to immobilization which indicates that affinity of the enzyme towards its substrate is reduced after immobilization. The finding is in agreement with Li et al (2001) who reported lower K m value after immobilization of papain on nitrilon fiber. The rate constant k 2 represents rate of breakdown of enzyme-substrate complex to product(s).…”
Section: Kinetic Study Of Protein Hydrolysis Using Aipsupporting
confidence: 95%
“…K m is increased 10 times due to immobilization which indicates that affinity of the enzyme towards its substrate is reduced after immobilization. The finding is in agreement with Li et al (2001) who reported lower K m value after immobilization of papain on nitrilon fiber. The rate constant k 2 represents rate of breakdown of enzyme-substrate complex to product(s).…”
Section: Kinetic Study Of Protein Hydrolysis Using Aipsupporting
confidence: 95%
“…When the enzyme reaction was carried out at 37 • C for 10 min with stirring, 3 ml of 5% trichloroacetic acid solution was added into the beaker flask, the reaction mixture was statically equilibrated at 25 • C for 1 h, and then it was filtered. The absorbance of the filtrate was measured at 280 nm [24]. One unit (U) of enzymatic activity was defined as the amount of enzyme increasing 0.001 absorbance/min at 280 nm in this condition [25].…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Papain has known to work effectively when immobilized in other different supports like on SiO 2 particles containing amine groups [8], alumina [9], nitrilon fiber carrier [10], and water soluble polymer polyvinyl alcohol [11]. Additionally, it is expected that an aerosol spray with formulated papain in pectin gel would not cause any drip.…”
Section: Introductionmentioning
confidence: 99%
“…In weight/volume terms, the enzyme preparations are seldom pure and it is expected that the enzyme source will be used in amounts from 0.001% by weight to 20% by weight formulation. Precise amounts will vary with purity of the enzyme [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%